Shape‐Anisotropic Microembolics Generated by Microfluidic Synthesis for Transarterial Embolization Treatment (Adv. Healthcare Mater. 10/2022). Issue 10 (18th May 2022) - Luo, Yucheng; Ma, Yutao; Chen, Zijian; Gao, Yanan; Zhou, Yuping; Liu, Xiaoya; Liu, Xuezhe; Gao, Xu; Li, Zhihua; Liu, Chuang; Leo, Hwa Liang; Yu, Hanry; et al.
Abstract : Shape‐Anisotropic Microembolics In article number 2102281, Qiongyu Guo and co‐workers develop anisotropically‐shaped particulate embolic agents with calibrated sizes using a facile droplet‐based microfluidic technique based on a heat‐accelerated crosslinking reaction. Compared to conventional spherical embolic particles, the capsule shape‐based nonspherical microembolics simultaneously enhance endovascular navigation, penetration depth, and embolization stability, demonstrating distinctive therapeutic effects of shape anisotropy for transcatheter embolotherapies.